2019
DOI: 10.1101/gad.325878.119
|View full text |Cite
|
Sign up to set email alerts
|

Maxdeletion destabilizes MYC protein and abrogates Eµ-Myclymphomagenesis

Abstract: Although MAX is regarded as an obligate dimerization partner for MYC, its function in normal development and neoplasia is poorly defined. We show that B-cell-specific deletion of Max has a modest effect on B-cell development but completely abrogates Eµ-Myc-driven lymphomagenesis. While Max loss affects only a few hundred genes in normal B cells, it leads to the global down-regulation of Myc-activated genes in premalignant Eµ-Myc cells. We show that the balance between MYC-MAX and MNT-MAX interactions in B cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 57 publications
7
38
0
Order By: Relevance
“…This is consistent with studies showing that MGA in association with PRC1.6 occupies E2F and MYC responsive genes in resting (G0) cells (Ogawa et al 2002). A large body of evidence implicates a critical role for MYC and E2F cooperation in maintaining normal tissue homeostasis (Pickering et al 2009, Liu et al 2015, Mathsyaraja et al 2019).…”
Section: Mga As a Myc And E2f Antagonist In Tumorssupporting
confidence: 85%
“…This is consistent with studies showing that MGA in association with PRC1.6 occupies E2F and MYC responsive genes in resting (G0) cells (Ogawa et al 2002). A large body of evidence implicates a critical role for MYC and E2F cooperation in maintaining normal tissue homeostasis (Pickering et al 2009, Liu et al 2015, Mathsyaraja et al 2019).…”
Section: Mga As a Myc And E2f Antagonist In Tumorssupporting
confidence: 85%
“…Noteworthy, B-cell-specific deletion of MAX has a modest effect on B-cell development but completely abrogates Eμ-myc -driven lymphomagenesis. Moreover, a study found that MAX loss leads to a significant reduction in MYC protein levels and down-regulation of direct transcriptional targets in premalignant Eμ-myc cells, including regulators of MYC stability [ 64 ]. Furthermore, the transcriptional repressor and MAX interactor MNT (MAX Network Transcriptional Repressor), competes with MYC for occupancy at E-box sequences in promoter regions [ 65 ].…”
Section: Transcriptional Regulation Network Involved In Myc-drivenmentioning
confidence: 99%
“…However, when Myc’s intracellular levels and functions change during tumor development is so far not well understood. In contrast to Myc, Max is a stable and abundant protein, which is not deregulated in cancer, albeit it is essential for Myc-driven lymphomagenesis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%